Application of the discontinous Galerkin time domain method to the optics of metallic nanostructures - Grynko, Yevgen; Förstner, Jens; Meier, Torsten (AAPP | Atti della Accademia Peloritana dei Pericolanti)
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. The model is used to compute the linear and nonlinear optical response of split ring resonators and to study physical mechanisms that contribute to second harmonic generation.
Keywords: tet_topic_numerics; tet_topic_shg; tet_topic_meta

Simulation of the ultrafast nonlinear optical response of metal slabs - Wand, Mathias; Schindlmayr, Arno; Meier, Torsten; Förstner, Jens (Physica Status Solidi B)
We present a nonequilibrium ab initio method for calculating nonlinear and nonlocal optical effects in metallic slabs with a thickness of several nanometers. The numerical analysis is based on the full solution of the time‐dependent Kohn–Sham equations for a jellium system and allows to study the optical response of metal electrons subject to arbitrarily shaped intense light pulses. We find a strong localization of the generated second‐harmonic current in the surface regions of the slabs.
Keywords: tet_topic_shg

Localised Phonon Modes at LiNbO3(0001) Surfaces - Sanna, S.; Berth, Gerhard; Hahn, W.; Widhalm, A.; Zrenner, Artur; Schmidt, Wolf Gero (Ferroelectrics)
The vibrational properties of the LiNbO3 (0001) surfaces have been investigated both from first principles and with Raman spectroscopy measurements. Firstly, the phonon modes of bulk and of the (0001) surface are calculated by means of the density functional theory. Our calculations reveal the existence of localised vibrational modes both at the positive and at the negative surface. The surface vibrations are found at energies above and within the bulk bands. Phonon modes localised at the positive and at the negative surface differ substantially. In a second step, the Raman spectra of LiNbO3 bulk and of the two surfaces have been measured. Raman spectroscopy is shown to be sensitive to differences between bulk and surface and between positive and negative surface. The calculated and measured frequencies are in agreement within the error of the method.

Injection currents in (110)-oriented GaAs/AlGaAs quantum wells: recent progress in theory and experiment - Duc, H. T.; Pochwala, M.; Förstner, Jens; Meier, Torsten; Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M. (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XV)
We experimentally and theoretically investigate injection currents generated by femtosecond single-color circularly-polarized laser pulses in (110)-oriented GaAs quantum wells. The current measurements are performed by detecting the emitted Terahertz radiation at room temperature. The microscopic theory is based on a 14 x 14 k • p band-structure calculation in combination with the multi-subband semiconductor Bloch equations. For symmetric GaAs quantum wells grown in (110) direction, an oscillatory dependence of the injection currents on the exciting photon energy is obtained. The results of the microscopic theory are in good agreement with the measurements.
Keywords: tet_topic_qw

Electron g-factor anisotropy in symmetric (110)-oriented GaAs quantum wells - Hübner, J.; Kunz, S.; Oertel, S.; Schuh, D.; Pochwała, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten; Oestreich, M. (Physical Review B)
We demonstrate by spin quantum beat spectroscopy that in undoped symmetric (110)-oriented GaAs/AlGaAs single quantum wells, even a symmetric spatial envelope wave function gives rise to an asymmetric in-plane electron Land´e g-factor. The anisotropy is neither a direct consequence of the asymmetric in-plane Dresselhaus splitting nor a direct consequence of the asymmetric Zeeman splitting of the hole bands, but rather it is a pure higher-order effect that exists as well for diamond-type lattices. The measurements for various well widths are very well described within 14 × 14 band k·p theory and illustrate that the electron spin is an excellent meter variable for mapping out the internal—otherwise hidden—symmetries in two-dimensional systems. Fourth-order perturbation theory yields an analytical expression for the strength of the g-factor anisotropy, providing a qualitative understanding of the observed effects.
Keywords: tet_topic_qw

Calculus-based optimization of the electron dynamics in nanostructures - Meier, Torsten; Reichelt, Matthias; Walther, A. (Photonics and Nanostructures - Fundamentals and Applications)
For numerous applications, the computation and provision of exact derivative information plays an important role for optimizing the considered system. This paper introduces the technique of algorithmic differentiation, a method to compute derivatives of arbitrary order within working precision. This derivative information will be combined with a calculus-based optimization algorithm to optimize a non-trivially shaped laser pulse which coherently steers the electron dynamics in a semiconductor quantum wire. Numerical results illustrating the cost for the derivative computation and the optimization process are presented and discussed.

Europa und die Welt 2020: Entwicklungen und Tendenzen

Ojalá viva el subjuntivo! – Grammatik und didaktische Transformation des subjuntivo für den Spanischunterricht - Bürgel, Christoph (Hispanorama)

Qu'est-ce que c'est génial! – Formate des kommunikativ-dialogischen Engagements - Bürgel, Christoph (Zeitschrift für Romanische Sprachen und ihre Didaktik)

Herz-Jesu-Verehrung. Ein Kult im Spannungsfeld von Frömmigkeit und Politik - Priesching, Nicole (Theologie, wohin? Blicke von außen und von innen)

Scms–semantifying content management systems - Ngonga Ngomo, Axel-Cyrille; Heino, Norman; Lyko, Klaus; Speck, René; Kaltenböck, Martin (The Semantic Web–ISWC 2011: 10th International Semantic Web Conference, Bonn, Germany, October 23-27, 2011, Proceedings, Part II 10)

Studium heute: Gesundheitsfördernd oder -gefährdend? Eine Lebensstilanalyse - Köster, Carolin; Brandl-Bredenbeck, Hans Peter; Kämpfe, Astrid (Dokumentation 16. Bundesweiter Kongress Armut und Gesundheit. Verwirklichungschancen für Gesundheit)

Measuring physical activity of children - Development of a new self-report questionnaire - Kämpfe, Astrid; Kehne, Miriam (Book of proceedings: Moving People, Moving Forward. World Congress of the International Association of Physical Education in Higher Education 2011)

(the ActiFE Study Group). Walking on sunshine: effect of weather conditions on physical activity in older people - Klenk, J.; Büchele, G.; Rapp, K.; Franke, Sebastian; Peter, R. (Journal of Epidemiology and Community Health. JECH Online First, published on February 15, 2011)

Theological Education Underground 1937-1939 - Bonhoeffer, Dietrich

HDL-Mutation Based Simulation Data Generation by Propagation Guided Search - Xie, Tao; Müller, Wolfgang; Letombe, Florian (Proceedings of Euromicro DSD 2011)
HDL-mutation based fault injection and analysis is considered as an important coverage metric for measuring the quality of design simulation processes [20, 3, 1, 2]. In this work, we try to solve the problem of automatic simulation data generation targeting HDL mutation faults. We follow a search based approach and eliminate the need for symbolic execution and mathematical constraint solving from existing work. An objective cost function is defined on the test input space and serves the guidance of search for fault-detecting test data. This is done by first mapping the simulation traces under a test onto a control and data flow graph structure which is extracted from the design. Then the progress of fault detection can be measured quantitatively on this graph to be the cost value. By minimizing this cost we approach the target test data. The effectiveness of the cost function is investigated under an example neighborhood search scheme. Case study with a floating point arithmetic IP design has shown that the cost function is able to guide effectively the search procedure towards a fault-detecting test. The cost calculation time as the search overhead was also observed to be minor compared to the actual design simulation time.
Keywords: Hardware design languages; Cost function; Computational modeling; Fault detection; Data models; Analytical models; Testing

Sexual Experience - Milkov, Nikolay (Sex, Love, and Friendship)

Schriftliches Argumentieren. Zur Ontogenese konzessiver Argumentationskompetenz - Rezat, Sara (Didaktik Deutsch)

Virtual Prototyping software-intensiver mechatronischer Systeme - Eine Fallstudie - Becker, Markus; Zabel, Henning; Müller, Wolfgang; Elfeky, Ahmed

Weihnachten - Die Geburt Jesu (Mt 1,18-2,23). Interpretationen - Unterrichtsmodell - Garske, Volker